2015
DOI: 10.1155/2015/963940
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pediatricians as Key Stakeholders in Influencing Immunization Policy Decisions for the Introduction of Meningitis B Vaccine in Canada: The Ontario Perspective

Abstract: Invasive meningococcal disease is a rapidly progressing infection that can lead to death within 24 h of onset or cause serious life-threatening disabilities. Serogroup B is now the most common form in Canada. In Ontario, the Pediatrics Section of the Ontario Medical Asso ciation and the Pediatricians Alliance of Ontario have developed five recommendations regarding immunization policy with a primary focus on providing the vaccine for children. The recommendations presented by the authors are intended to assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…[4][5][6][7] Based on the report of the World Bank, the vaccines covered by Expanded Program on Immunization (EPI) is one of the available measures most cost-effective interventions, with measles immunization estimated $10 per year of life with disabilities (DALY) prevented, and the Diphtheria-Pertussis-Tetanus (DPT) vaccinations $25 per DALY prevented. [8][9][10] One recent analysis showed that the incremental cost per death averted of EPI is about $478 in East Asia and Pacific, $274 in South Asia, and $1754 in Central Asia and Europe in 2001. 6,[11][12][13] EPI was first mentioned in Vietnam in 1981, and became one of six health plans national target program in 1985.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Based on the report of the World Bank, the vaccines covered by Expanded Program on Immunization (EPI) is one of the available measures most cost-effective interventions, with measles immunization estimated $10 per year of life with disabilities (DALY) prevented, and the Diphtheria-Pertussis-Tetanus (DPT) vaccinations $25 per DALY prevented. [8][9][10] One recent analysis showed that the incremental cost per death averted of EPI is about $478 in East Asia and Pacific, $274 in South Asia, and $1754 in Central Asia and Europe in 2001. 6,[11][12][13] EPI was first mentioned in Vietnam in 1981, and became one of six health plans national target program in 1985.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries quadrivalent and or monovalent meningococcal vaccinations are reimbursed, although serogroup A, C, W135, Y epidemiology is significantly lower than that of men B. Indeed, recently Yamashiro et al [1], discussed this point of view in the case of Ontario (CA), pointing out that the rationale of Bexsero's exclusion from reimbursement scheme is difficult to explain and has perhaps potential legal implications. This is because routine recommendations and funding are currently in place for meningococcal serogroups that cause significantly less disease in Canada, which in return inflates parents' confusion about which vaccination (A, C, W135, Y or B) is of higher priority based on the current epidemiological landscape of their region.…”
Section: Descriptionmentioning
confidence: 99%
“…Accumulating evidence has suggested that pediatricians play a significant role in foster parental acceptability of vaccinations when they provide accurate educational messages and promote immunization compliance [14,15]. However, limited attention has been paid to investigating knowledge of healthcare providers, especially pediatricians, toward vaccination against MenB in infants, children, and young adults [15,16,17].…”
Section: Introductionmentioning
confidence: 99%